TUBERCULOSIS AND CHRONIC RESPIRATORY DISEASE : A SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Tuberculosis, also known as TB, is one of the most common infectious illnesses and has emerged as a major global public health concern. According to statistics provided by the World Health Organization (WHO), there are around 8.6 million new cases of tuberculosis each year, and the disease is responsible for 1.3 million fatalities. More than a half a million cases are documented in youngsters, and an estimated 320,000 fatalities are attributed to those who are infected with HIV. To this day, infectious diseases remain the leading cause of death across the globe, with tuberculosis being the infectious disease that is responsible for the greatest number of deaths overall. This is especially true in nations that are still developing and nations that are emerging. Despite the fact that tuberculosis can show in any organ or tissue, the respiratory system is the site where the illness is most commonly found to be actively spreading. Lungs and airways are both affected by disorders that affect the respiratory system. According to the World Health Organization (WHO), chronic respiratory diseases are responsible for the premature deaths of 4.6 million people each year, which accounts for more than 5% of global mortality. Approximately 90% of these deaths take place in low- and middle-income countries. The findings of this study's search suggested that the prevalence of individuals diagnosed with COPD was noticeably high among patients who had signs of pulmonary TB or who had recovered from pulmonary tuberculosis. There is a dearth of data about other disorders, such as bronchiectasis and bronchitis.